Demand Elasticities for Selected Seasoning Commodities: An Almost Ideal Demand System with Instrumental Variables - Fathul Muin, Muhamad (Estudios de Economía, 2025)
This study analyzes the consumption elasticities of five key seasoning commodities in Indonesia: cooking oil, red onion, garlic, red chili, and cayenne pepper. A Linear Approximate Almost Ideal Demand System (LA/AIDS) model is employed, incorporating instrumental variables to address potential endogeneity. The results indicate that the unconditional income and own-price elasticities are inelastic, with income elasticities ranging from 0.74 to 0.75 and own-price elasticities from –0.77 to –0.94. No significant evidence of substitution or complementarity among the seasonings is found. Furthermore, elasticity remain similar before and after the COVID-19 pandemic, and across regions with different economic sizes. However, regions known for spicy cuisines demonstrate higher elasticities than those with milder culinary traditions.